Kaleidoscope : the art of illustrative storytelling. (Sandu Publishing Co., 2018)
"Derived from magazines, posters, books, blogs and personal projects, Kaleidoscope includes interviews with six talented and enthusiastic masters of their art. Similar to a kaleidoscope, a good story also employs reflection on the different elements to create a narrative or pattern that is captivating to the reader. The result relies heavily on the artist s ability to turn the lens just right and capture the essentials of setting characterisation, mood, detail, motion and more to convey the intended meaning"--Publisher's description